2019
DOI: 10.14295/bds.2019.v22i2.1622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different surface treatments on color and translucency of bilayered translucent nano-crystalline zirconia before and after accelerated aging

Abstract: Objective: Despite the higher translucency of nano-crystalline Y-TZP than the conventional Y-TZP, it couldn’t be used in the anterior region of the mouth in its fully anatomical form without veneering for better esthetics. This study evaluated the color change (ΔE) and translucency parameter (TP) of the bilayered nano-crystalline zirconia restorations after different treatments of the zirconia surface before and after accelerated aging. Material and Methods: Forty samples of inCoris TZI were cut in the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Chemical surface treatments can also increase bond strength during crowns cementation [26]. Few studies have shown that a tribochemical silica-coated (TSC) [27][28][29][30] or a functional monomer of 10-methacrylixydecyl dihydrogen phosphate (MDP) [31] can increase the bond strength between cement and ceramic crowns. New zirconia cementation protocols use selfadhesive resin cements and new universal adhesives that contain MDP, producing Y-TZP crowns with stable and durable bond strength [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical surface treatments can also increase bond strength during crowns cementation [26]. Few studies have shown that a tribochemical silica-coated (TSC) [27][28][29][30] or a functional monomer of 10-methacrylixydecyl dihydrogen phosphate (MDP) [31] can increase the bond strength between cement and ceramic crowns. New zirconia cementation protocols use selfadhesive resin cements and new universal adhesives that contain MDP, producing Y-TZP crowns with stable and durable bond strength [32][33][34].…”
Section: Introductionmentioning
confidence: 99%